Killip and Kimball classification in the Ultrasound era: Is it time to redefine? - Ponce Gallegos, Marco Antonio (2024)
Lung ultrasound is a tool that is increasingly gaining strength in the initial evaluation of the patient in the emergency department and in critical care areas, making it particularly useful for cardiologists. In patients with ST elevation and acute myocardial infarction it has been observed that 25-45% of patients are wrongly classified as Class I in the Killip and Kimball classification after lung ultrasound (subclinical congestion). The clinical relevance of this finding lies in the fact that the greater the number of B lines, the greater short- and long-term the mortality is. An important advantage is that no prolonged time for learning the technique is required. More studies are needed to evaluate the role and importance of subclinical congestion in patients with acute myocardial infarction. Unfortunately, ultrasound is not widely available in developing countries, so the physical examination will continue to play an important role in the initial evaluation of patients with acute myocardial infraction.